Quercetin is protective against short‐term dietary advanced glycation end products intake induced cognitive dysfunction in aged ICR mice - Yang, Shengyi; Zhou, Huanhuan; Wang, Guiping; Zhong, Xiao‐Hong; Shen, Qi‐Liang; Zhang, Xue‐Jing; Li, Ru‐Yi; Chen, Li‐Hua; Zhang, Ya‐Han; Wan, Zhongxiao (Journal of food biochemistry, 2020)
Dietary advanced glycation end products (dAGEs) might be potential toxins involved in the pathogenesis of Alzheimer’s disease (AD). Quercetin is a flavonoid possessing neuroprotective effects. We aimed to explore whether a 21 days of dAGEs intake would result in cognitive dysfunction in aged ICR mice, and the protective effects of quercetin, with potential mechanisms explored. Fourteen‐month old ICR mice were randomly assigned into four groups, that is, Control, AGEs, quercetin, and AGE diet supplemented with quercetin. Key markers involved in Aβ, tau, and neuroinflammation from hippocampus and cortex were measured via western blot. Gut microbiota and short chain fatty acids profiles from intestinal contents were measured via 16S rRNA gene sequencing and gas chromatography (GC), respectively. Quercetin alleviated cognitive impairment induced by dAGEs in aged mice. This might be associated with that quercetin reduced cathepsin B, tau phosphorylation, and neuroinflammation, and elevated α‐diversity index (ACE, Chao1, and Shannon index), and reduced phylum Verrucomicrobia of gut microbiota. Practical applications Alzheimer’s disease (AD) has been regarded as the commonest cause of progressive dementia for the elderly. This study is the very first to demonstrate that even a short‐term dietary advanced glycation end product (dAGEs) intake induced impaired cognitive function in aged ICR mice, and querectin is capable of reversing dAGEs‐induced cognitive dysfunction. Reduced tau phosphorylation, neuroinflammation, and altered gut microbiota profiles may be involved in querectin’s protective effects against dAGEs‐induced cognitive impairment. Our study suggested that quercetin supplementation might be beneficial for improving cognitive function in elderly subjects with high consumption of dAGEs such as grilling, frying, and broiling of food. A 21 days diet rich in AGEs resulted in impaired cognitive function in aged ICR mice, while quercetin intervention improved the cognitive function. Reduced tau phosphorylation and neuro‐inflammation, and elevated gut microbiota α‐diversity index (i.e., ACE, Chao1 and Shannon), as well as reduced phylum Verrucomicrobia of gut microbiota might be partially responsible for improved cognitive function post querectin intervention.